Lipid-polymeric films: composition, production and applications in wound healing and skin repair - Souto, Eliana B. (2021)
The use of lipids in the composition of polymeric-based films for topical administration of bioactive ingredients is a recent research topic; while few products are commercially available, films containing lipids represent a strategic area for the development of new products. Some lipids are usually used in polymeric-based film formulations due to their plasticizing action, with a view to improving the mechanical properties of these films. On the other hand, many lipids have healing, antimicrobial, anti-inflammatory, anti-aging properties, among others, that make them even more interesting for application in the medical-pharmaceutical field. This manuscript discusses the production methods of these films both on a laboratory and at industrial scales, the properties of the developed biopolymers, and their advantages for the development of dermatologic and cosmetic products.